Survival or Revival: Long-Term Preservation Induces a Reversible Viable but Non-Culturable State in Methane-Oxidizing Bacteria - Hoefman, Sven; Van Hoorde, Koenraad; Boon, Nico; Vandamme, Peter; De Vos, Paul; Heylen, Kim (PLOS ONE, 2012)
Knowledge on long-term preservation of micro-organisms is limited and research in the field is scarce despite its importance for microbial biodiversity and biotechnological innovation. Preservation of fastidious organisms such as methane-oxidizing bacteria (MOB) has proven difficult. Most MOB do not survive lyophilization and only some can be cryopreserved successfully for short periods. A large-scale study was designed for a diverse set of MOB applying fifteen cryopreservation or lyophilization conditions. After three, six and twelve months of preservation, the viability (via live-dead flow cytometry) and culturability (via most-probable number analysis and plating) of the cells were assessed. All strains could be cryopreserved without a significant loss in culturability using 1% trehalose in 10-fold diluted TSB (TT) as preservation medium and 5% DMSO as cryoprotectant. Several other cryopreservation and lyophilization conditions, all of which involved the use of TT medium, also allowed successful preservation but showed a considerable loss in culturability. We demonstrate here that most of these non-culturables survived preservation according to viability assessment indicating that preservation induces a viable but non-culturable (VBNC) state in a significant fraction of cells. Since this state is reversible, these findings have major implications shifting the emphasis from survival to revival of cells in a preservation protocol. We showed that MOB cells could be significantly resuscitated from the VBNC state using the TT preservation medium.